2022
DOI: 10.1001/jama.2022.18590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ivermectin vs Placebo on Time to Sustained Recovery in Outpatients With Mild to Moderate COVID-19

Abstract: ImportanceThe effectiveness of ivermectin to shorten symptom duration or prevent hospitalization among outpatients in the US with mild to moderate symptomatic COVID-19 is unknown.ObjectiveTo evaluate the efficacy of ivermectin, 400 μg/kg, daily for 3 days compared with placebo for the treatment of early mild to moderate COVID-19.Design, Setting, and ParticipantsACTIV-6, an ongoing, decentralized, double-blind, randomized, placebo-controlled platform trial, was designed to evaluate repurposed therapies in outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 13 publications
1
44
1
Order By: Relevance
“…17,18 Recent results from the current platform trial reported participants receiving ivermectin, with a 400 µg/kg, daily for 3 days had a an average ~12-hour shorter time spent unwell when compared with placebo, a secondary outcome for the trial. 15 This finding was not replicated here.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…17,18 Recent results from the current platform trial reported participants receiving ivermectin, with a 400 µg/kg, daily for 3 days had a an average ~12-hour shorter time spent unwell when compared with placebo, a secondary outcome for the trial. 15 This finding was not replicated here.…”
Section: Discussioncontrasting
confidence: 61%
“…The notable difference in baseline characteristics between these 2 cohorts is the completed vaccination rate, which is 84% for this study and was 47% for the prior ivermectin 400 µg/kg group. 15 Hospitalizations and COVID-19-related clinical events were less common in this largely vaccinated cohort. The incidence of acute care visits, hospitalizations, or death was similar with ivermectin (5.7%) and placebo (6.0%); a result also observed in the two prior ivermectin 400 μg/kg randomized trials in the US.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Additionally, 15 repurposed drugs tested in 23 outpatient RCTs were included in our analysis for context: metformin 13 , fluvoxamine 13, 34, 35 , ivermectin 13, 36, 37, 38 , hydroxychloroquine 33, 39, 40, 41, 42 , nitazoxanide 43 , colchicine 44 , niclosamide 45 , four antithrombotics-aspirin, apixaban 46 , sulodexide 47 , enoxaparin 48, 49 , inhaled ciclesonide 50 , the herbal mixture Saliravira 51 , azithromycin 52, 53 , and resveratrol 54 .…”
Section: Resultsmentioning
confidence: 99%